Molecular epidemiological investigation of group A porcine rotavirus in East China - Tao, Ran; Chang, Xinjian; Zhou, Jinzhu; Zhu, Xuejiao; Yang, Shanshan; Li, Kemang; Gu, Laqiang; Zhang, Xuehan; Li, Bin (Frontiers in Veterinary Science, 2023)
Group A porcine rotavirus (RVA) is a serious threat to the breeding industry worldwide, which was associated with severe diarrhea in piglets. However, the prevalence and molecular characterizations of RVA circulating in farms of East China remains largely unknown. Five hundred and ninety-four samples were collected from thirty-five farms in East China from 2017 to 2019. The results showed that 16.8% was positive for RVA, among different types of samples, the highest positive rate of RVA was intestinal samples (19.5%), and among pigs at different growth stages, the highest detection rate of RVA in piglets was 18.5%. Furthermore, the VP7 and VP4 genes of nine positive samples were sequenced for alignment and phylogenetic analysis. Phylogenetic analysis revealed that the nine isolates belong to four kinds of genotype combinations correspondingly: G9P[7](5/9), G5P[13](2/9) , G9P[13](1/9), and G5P[7](1/9) , which suggested that multiple genotypes combinations of RVA were circulating in pigs in East China. Thus, it’s necessary to continuously survey the prevalence of RVA in pigs, aiding the rational application of vaccines or other measures for the prevention and control of RVA spread.